Computational evaluation of long-term ravelling susceptibility of Permeable Friction Courses (PFC). (12th July 2021) - Caro, Silvia; Manrique-Sanchez, Laura; Kim, Yong-Rak
Highlights: We used FE and CZE modelling to assess long-term ravelling in PFC mixtures. 2D PFC microstructures were randomly generated using DE gravimetric methods. The models evaluated traffic speed and braking, load magnitude, and environmental effects. Multiple microstructures were assessed to account for PFC heterogeneity. Low speed traffic and vehicle braking are main factors boosting raveling. Abstract: Ravelling is a main distress in Permeable Friction Courses (PFC). This damage process is enhanced by the presence of moisture and ageing, which further reduces the overall durability of the mixtures. This study uses Finite Element (FE) methods to assess long-term ravelling susceptibility of PFC. Different two-dimensional (2D) PFC microstructures were randomly generated through a Microstructure Generator (MG) and Discrete Element (DE) gravimetric methods. These microstructures were located on top of a conventional pavement and subjected to a moving wheel load under different traffic operation conditions. PFC ravelling was assumed to occur at the asphalt mortar located at the stone-on-stone contacts. The linear viscoelastic and fracture properties of the PFC asphalt mortar were experimentally obtained after subjecting the material to long-term ageing conditions and multiple water moisture cycles, which represent several in-service years. Zero thickness Cohesive Zone Elements (CZE) were included within the mortar-mortar contacts of the PFC to better quantify the potential initiation of ravelling. The results show that the ravelling susceptibility of a PFC is drastically affected by the loading conditions (e.g., load magnitude, vehicle breaking over the pavement, vehicle speed) and the environmental and mechanical degradation of the asphalt mortar when subjected to in-service conditions.